THE Effect of the Local Wisdom based of Think Pair Share (TPS) Learning Model toward Students' Result of Social Learning at Grade IV SDN 21 Pulau Punjung - Husni, Raudatul; Sari , Fitria; Anisa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
This research is motivated by student learning outcomes in social studies learning, there are still many who have not reached the KKM. This type of research is a Pre-Experimental Design research, with a quantitative approach and the form of design using the Quasi-Experimental Method Non-Equivalent Group Pre-test Post-test Design. The subjects of this study were fourth grade students of SDN 21 Pulau Punjung. The sampling of this research used the Probability Sampling (Randomly) technique, which consisted of 44 students. Data collection techniques were carried out by using test and non-test techniques. The data collection tool is in the form of multiple choice questions obtained by 25 pre-test and post-test items through validation tests and reliability tests. Data analysis used the Normality Test, Homogeneity Test and Hypothesis Test/t-test which was processed using SPSS 22. The results of the hypothesis calculation obtained were sig < (0.000 <0.05) which means the t-test rejected the existence of H0 and accepted the Ha contained. Application of the Think Pair Share (TPS) Model Based on Local Wisdom to the Social Studies Learning Outcomes of Fourth Grade Students of SDN 21 Pulau Punjung